The effects of altitude training on the muscle strength and the aerobic capacity of elite kayakists - Sun, X. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
To investigate the effects of altitude training on the development of elite kayakists` muscle strength and aerobic capacity.